2019
DOI: 10.1128/iai.00731-18
|View full text |Cite
|
Sign up to set email alerts
|

A Glucuronoxylomannan Epitope Exhibits Serotype-Specific Accessibility and Redistributes towards the Capsule Surface during Titanization of the Fungal Pathogen Cryptococcus neoformans

Abstract: Disseminated infections with the fungal species Cryptococcus neoformans or, less frequently, Cryptococcus gattii are an important cause of mortality in immunocompromised individuals. Central to the virulence of both species is an elaborate polysaccharide capsule that consists predominantly of glucuronoxylomannan (GXM). Due to its abundance, GXM is an ideal target for host antibodies, and several monoclonal antibodies (mAbs) have previously been derived using purified GXM or whole capsular preparations as antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…The C. neoformans cell wall is covered by a protective capsule, which not only impairs phagocytosis by macrophages, but also mask PAMPs from being engaged by host PRRs (53). Moreover, H99 titan cells have been reported to have altered capsule compared to yeast (5, 54). We have previously demonstrated that Crp127 is an anti-capsule monoclonal IgM (Immunoglobulin M) antibody associated with O-mannosylation, to capsular polysaccharide and that its localization is dynamic throughout titan development (54).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The C. neoformans cell wall is covered by a protective capsule, which not only impairs phagocytosis by macrophages, but also mask PAMPs from being engaged by host PRRs (53). Moreover, H99 titan cells have been reported to have altered capsule compared to yeast (5, 54). We have previously demonstrated that Crp127 is an anti-capsule monoclonal IgM (Immunoglobulin M) antibody associated with O-mannosylation, to capsular polysaccharide and that its localization is dynamic throughout titan development (54).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, H99 titan cells have been reported to have altered capsule compared to yeast (5, 54). We have previously demonstrated that Crp127 is an anti-capsule monoclonal IgM (Immunoglobulin M) antibody associated with O-mannosylation, to capsular polysaccharide and that its localization is dynamic throughout titan development (54). We therefore assessed the capsule of Zc isolates after titan induction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Titan cell formation and the role of SGs found in extracellular vesicles (EVs) are important features that can be tied into how the fungal cells respond and trigger protection in the host. Titanization is the enlargement of the surrounding capsule of C. neoformans when grown in minimal media or the hostile host environment [90][91][92]. Since SGs are found in the plasma membrane, the multi-fold enlargement of the capsule may hinder or ablate the physical properties SGs convey to the capsule, but this is purely speculation, since this has not been investigated as well and is not currently under investigation by our group.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%